Mild Acidic Charcoal Catalyzed Synthesis of 3,4-dihydropyrimidin-2(1H)-one/-thione Derivatives - Rajendra Patil; Jagdish Chavan; Shivnath Patel; Vaishali Shinde; Anil Beldar (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2022)

(untitled)
A green and efficient method for the multicomponent synthesis of 3,4-dihydropyrimidin-2(1H)-ones and -thiones using acetic acid supported on activated charcoal as a mild acid catalyst in ethanol under both conventional as well as microwave irradiation conditions has been developed. The catalyst system found more efficient under microwave irradiation conditions than conventional conditions with shorter reaction times and excellent yields.